PEMBENTUKAN KARAKTER DISIPLIN MELALUI KEGIATAN EKSTRAKURIKULER PASKIBRA DI KELAS XI SMA NEGERI 9 PONTIANAK - Makhyani Makhyani; Rustiyarso Rustiyarso; Izhar Salim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe title of this research was "An Implementation Analysis of Students' Discipline Character Building by the Coach through Paskibra Activity on Class XI of SMAN 9 Pontianak". The research purpose were to find out (1) Plan of Discipline Character Building, (2) Implementation of Discipline Character Building, and (3) Result of Students' Discipline Character Building by the Coach through Paskibra Activity on Class XI of SMAN 9 Pontianak. The method in this research was qualitative descriptive. The technique in collecting the data were observation, interview and documentation, therefore the tool of data collection were observation guideline, interview guideline and documentation tool. (1) activity plan such rules, time schedule and work program (2) implementation of discipline character building was conducted through time discipline and obey the rules discipline, the good example like attend on time, and give warning to disobedient students. (3) result of the activity could be seen through evaluation such giving motivation and advice, and attending the competition. The coach built the character using two methods, they were negative discipline such punishment or strict sanction, and positive discipline such giving advice, giving procedure and giving good example and also the firm evaluation. Key words: Extracurricular Activity, Paskibra, Discipline Character Building